2014
DOI: 10.1111/ajag.12141
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of faecal incontinence in community-dwelling older people in Bali, Indonesia

Abstract: Conclusion: Faecal incontinence is common among community-dwelling older people inBali.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…Indonesia and Malaysia share same culture, and the study also used a similar method that was utilized in this one to diagnose chronic constipation. 4 The researchers concluded that the difference in the results may be due to our study population consisting of elderly patients with poorer health status.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Indonesia and Malaysia share same culture, and the study also used a similar method that was utilized in this one to diagnose chronic constipation. 4 The researchers concluded that the difference in the results may be due to our study population consisting of elderly patients with poorer health status.…”
Section: Discussionmentioning
confidence: 92%
“…In previous studies, the prevalence of chronic constipation was higher among older people in Western countries 5,[16][17][18] than in Asia (21% to 75% vs. 16.5% to 25.8%). 4,9,19,20 Previous studies suggested that a high prevalence was probably due to the study population consisting of high-risk populations, such as nursing home residents 16,21 and women, 5 and the use of self-reporting or questionnaires. 1 A study of older people's households in Indonesia found that the prevalence was 16.5%, which was lower than of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of older adult populations spanned 8 countries with seven studies conducted in US populations (see Table 2). [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] The prevalence of chronic constipation has ranged widely from 4% in Indonesia [72] to 25.8% in Korea. [73] For any constipation, prevalence has ranged from 4.4% in Spain [74] to 44.5% in the USA.…”
Section: Prevalence Estimates In Older Adult Populationsmentioning
confidence: 99%
“…Data diolah dengan uji Chisquare dan tingkat signifikansi p<0,05. Hasil: Hasil penelitian ini menunjukkan bahwa paritas 3, riwayat persalinan vakum dan riwayat kala II lama berhubungan secara bermakna dengan kejadian inkontinensia ani di mana nilai p masing-masing 0,026 dengan OR (95%CI)= 1,8 (1,07-3,03), p= 0,018 dengan OR (95%CI)= 3,65 (1,2-10,7) dan p= 0,006 dengan OR (95%CI)= 2,91 (1,(2)(3)(4)(5)(6)7). Riwayat episiotomi dan persalinan bayi 4000 gram tidak memiliki hubungan bermakna dengan inkontinensia ani.…”
unclassified